(untitled) (American International Journal of Education and Linguistics Research, 2019)
This study examines the Knowledge level of teachers in Ibadan on global warming, the factors influence it and how they perceived it. Questionnaire was used as the main instrument for data collection. It was designed to elicit information on the basis of research questions set for this study. A total number of 450 teachers were used as the sample size. Descriptive statistics such as simple percentages and frequency counts were used in the analysis of the research data collected. The study revealed that teachers have knowledge on global warming and aware of its threat to human existence. It was observed that the source of their knowledge on global warming by teachers include the media and attendance at conferences and workshops. As a result of the above findings, it was recommended that efforts should be made to make relevant and up-to-date information on global warming available to the teachers. Emphasis should be made to make the teachers participate in programmes that address adaptation policies on global warming.